Factores de capital social que influyen en la construcción de asociatividad en la economía popular y solidaria en el sector de transporte de la ciudad de Latacunga. - Jiménez Álvarez, Verónica Maribel (2020)
The present research goal was to propose strategies that allow Social Capital and Associativity strengthening in the transport sector. This is similar to Popular and Solidarity Economy organizations’ section. This action is presented as a response to the problems observed in Social Capital construction in the transport cooperatives at La Matriz parish in Latacunga Canton, where certain skills are detected such as: relevance lack on union members’ section, inappropriate use of technological means, weakness in communication, and in interpersonal relationships, as well as training absence, and to this added unawareness on the legal structure in execution field, which causes weak structures for Associativity.A quantitative approach as methodology was designed in order to achieve this research. Also, the techniques applied were direct observation, participant observation and the survey. In addition, two instruments were structured, one addressed to the legal representatives with 56 questions and another addressed to Transport Cooperatives members with 52 questions, under the liker scale design. Besides, a random sample allowed to determine the Social Capital and associative performance dimensions with 200 members from a total population of 500 and 24 associations with their 24 leaders respectively. The research method was the analytical one and as a synthesis of the relevant results. It was determined that the training variable turns out to be significant with the university studies criterion, with which those members with greater training report lower levels of Social Capital, which may be related to the need for another training category, which does not correspond to hard skills of theoretical knowledge terms, but rather more applied ones, which let the day-to-day development of the operation. This actions allow to build trust, networks and relationships between members. In other words, it is why that a training plan is proposed for members to strengthen their capacities and business management